Pleomorphic adenoma of the external auditory canal - Sushma Aradhya; Namratha Ravishankar; Suchitha Satish (Autopsy and Case Reports, 2023)
Pleomorphic adenoma (PA) of the external auditory canal (EAC) is a rare clinical entity with a few cases reported in the literature. The clinical diagnosis of these lesions can be formidable due to their rarity and unusual location. This tumor occurs at various other anatomical locations apart from the major salivary glands. A 30-year-old female presented with a two-year history of a gradually enlarging and painless mass in the left external auditory canal. The tumor was excised, and histopathological and immunohistochemical evaluation revealed a mixed tumor with both epithelial and stromal components of different proportions, recognized and classified today by the World Health Organization (WHO) as a pleomorphic adenoma. The post-operative course was uneventful, and at the 10-month follow-up, no recurrence of the pleomorphic adenoma was noted. We highlight the histological features and the immunohistochemical profile of the tumor and review the literature on glandular neoplasms of the EAC and their recent classification, emphasizing on the histogenesis, clinical presentations, and microscopic features of the tumor. In addition, we aim to discuss vital features in differentiating these tumors from other tumors of the external auditory canal to enable clinicians and pathologists to recognize this uncommon benign neoplasm.